The trouble with May Amelia [compact disc, unabridged] - Holm, Jennifer L. (Random House/Listening Library, 2012)
Living with seven brothers and her father, who thinks girls are useless, a thirteen-year-old Finnish American farm girl is determined to prove her worth when a enterprising gentleman tries to purchase their cash-strapped family settlement in Washington State in 1900.